Sustainable development and environmental science - Kumar, Arvind, 1953-; Sivakami, R., 1969- (New Delhi : Daya Publishing House, 2013)
Contributed papers with reference to India.
Includes bibliographical references and index.
Keywords: Environmental management -- India; Human ecology -- India; Sustainable development -- India